The manufacturing adaptive capabilities of firms: the role of technology, market and management systems-related adaptive capabilities - Keskin, Halit; Akgun, Ali E.; Esen, Emel; Yilmaz, Tamer (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose This study investigates the roles of market, technology, and management system-related adaptive capability variables on a firm's manufacturing adaptive capability. In addition, the study examines the effects of a firm's manufacturing adaptive capability on its effectiveness. Further, this study tests the moderating role of organizational redundancy on the relationship between the market, technology, and management system-related adaptive capabilities and the overall manufacturing adaptive capability of a firm. Design/methodology/approach This study utilizes questionnaire-based research to test the suggested hypotheses by gathering related data from 59 manufacturing firms. Findings This study determined that a firm's technology and management system-related adaptive capability positively relates to firm's manufacturing adaptive capability. Further, market adaptive capability influences manufacturing adaptive capability via the levels of technology and management system-related adaptive capabilities. Manufacturing adaptive capability is also found to be positively associated with organizational effectiveness, and resource redundancy positively moderates the relationship between management systems adaptive capability and manufacturing adaptive capability. Conversely, resource redundancy negatively moderates the relationship between technology adaptive capability and manufacturing adaptive capability. Finally, this study demonstrates that information redundancy does not moderate the desired relationship between all the adaptive capability-related variables for firms. Research limitations/implications This study has some limitations inherent in survey design, mainly for both convenient sampling and country context. Practical implications This study suggests that management should improve firm's manufacturing adaptive capability to enhance firm's overall effectiveness. For that purpose, managers should consider the interrelationships between the market and a firm's technology, management system, and manufacturing-related adaptive capabilities. Management should also consider the importance of using resource-related redundancy to leverage the relationship between a firm's management adaptive capability and manufacturing adaptive capability. At the same time, management should be aware of certain reverse effects of resource redundancy on both technology adaptive capability and the manufacturing adaptive capability linkage of a firm. Originality/value This study expands the understanding of the adaptive capability of firms by examining how manufacturing adaptive capability can be further enhanced. The study also offers a model for the potential relationships that develop between different aspects of organizational adaptive capability by applying the contingency role of organizational redundancy variables.
Keywords: Adaptive capability; Manufacturing management; Organizational effectiveness; Organizational capabilities; Organizational redundancy; DYNAMIC CAPABILITIES; PERFORMANCE; AMBIDEXTERITY; INNOVATION; RESOURCE; ANTECEDENTS; FLEXIBILITY; ORIENTATION; COMPETENCE; STRATEGY; Engineering; Business & Economics